2001
DOI: 10.1007/s002040000188
|View full text |Cite
|
Sign up to set email alerts
|

DNA breaks and cell cycle arrest induced by okadaic acid in Caco-2 cells, a human colonic epithelial cell line

Abstract: Okadaic acid (OA) is a shellfish toxin produced by dinoflagellates, in mussels. It is a potent tumour promoter and represents a potential threat to human health even at low concentrations. OA targets mainly the gastrointestinal tract in acute poisoning, causing diarrhoea. Therefore the present investigations were designed to study the ability of okadaic acid to induce cytotoxicity and DNA lesions in a human colonic cell line (Caco-2). Incubation of Caco-2 cells with OA (3.75-60 ng/ml, i.e. 4.6 x 10(-3)-7.5 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…OA has also been reported to induce DNA fragmentation (Traoré et al, 2001;Huynh-Delerme et al, 2003;Parameswaran et al, 2004;Pinto-Silva et al, 2005). This is partly confirmed by the present data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…OA has also been reported to induce DNA fragmentation (Traoré et al, 2001;Huynh-Delerme et al, 2003;Parameswaran et al, 2004;Pinto-Silva et al, 2005). This is partly confirmed by the present data.…”
Section: Discussionsupporting
confidence: 92%
“…This time instead of simple DNA fragmentation, apoptosis has been elicited, suggesting for these additive effects at least three mechanisms: (i) genotoxicity of OA is exaggerated and generates too much DNA lesions, leading to cell cycle arrest via a p53-independent mechanism (Traoré et al, 2001;Le Hegarat et al, 2004;Pinto-Silva et al, 2005). In the present case apoptosis generated by OA alone (Traoré et al, 1999(Traoré et al, , 2001Pinto-Silva et al, 2005) has not been observed likely because the number of cells undergoing apoptosis was too low to be detected by agarose gel electrophoresis or by acridine orange staining. (ii) Addition of genotoxic effect of OA, Cd, and Cr (Leonard et al, 2004) overcomes the repair capacity of Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSP toxins include okadaic acid (OA), the dinophysistoxins-1 -2, and -3 and derivative forms (Blanco et al, 2005;García et al, 2010). Okadaic acid was described to be a powerful inhibitor of phosphatases type 1 and 2A, tumour promoter and apoptosis inductor in mammal cell lines (Cabado et al, 2004;Lago et al, 2005;Lerga et al, 1999;Rossini et al, 1997;Traoré et al, 2001;Valdiglesias et al, 2010). However, information concerning the effect of the DSP toxins on bivalves needs to be improved (Carvalho Pinto-Silva et al, 2003;Flórez-Barrós et al, 2011;Galimany et al, 2008aGalimany et al, , 2008bGalimany et al, , 2008cHégaret et al, 2011;Hégaret and Wikfors, 2005;Malagoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The LDH activity was measured by a colorimetric cytotoxicity detection kit (LDH) (Roche Diagnostics, Indianapolis, IN) according to manufacturer's instructions. The absorbance was read at 490/600 nm wavelength in microplate reader Determination of cell death by apoptosis DNA fragmentation assay: DNA fragmentation assay was performed as described by Traore et al (2001) and Wu et al (2004) with some modifications. Caco-2 cells were treated with legume extracts at 1.5, 3, 6 and 12 mg mLG 1 for 24 h. After incubation, 500 μL of lysis buffer (10 mm Tris-HCl, pH 8/5 mM EDTA/0.6% Triton X-100) was added to cells to release nuclear contents.…”
Section: Methodsmentioning
confidence: 99%